Mammillary body lesions and restricted subicular output lesions produce long-lasting DRL performance impairments in rats. - Tonkiss, J; Rawlins, J (1992)
Rats given either electrolytic lesions of the mammillary bodies (MB), transection of the descending columns of the fornix (DCF), transection of fibres projecting from subiculum to ventral striatum (SC) or sham operations (SO) were tested in three DRL experiments. DRL-18 efficiency was impaired significantly in MB rats, and non-significantly in DCF and SC rats. Analysis of timing behaviour revealed modifications in all three lesion groups, with a unique pattern in the SC group. DRL-36 efficiency was significantly impaired in all three lesion groups; the SC group again showed a unique timing pattern. Finally we assessed retention of DRL-36 in SO rats given mammillary body lesions. There was a lesion-induced impairment, smaller than that seen with postoperative training. We propose that the subicular output plays an important part in normal DRL performance; that the subicular outputs to the mammillary bodies and ventral striatum play independent roles in DRL; and that the effects of mammillary body lesions resemble those of hippocampal lesions because of the important functional relationship between subiculum and the mammillary bodies.